High diagnostic yield and novel variants in very late-onset spasticity. (2nd January 2019) - Almomen, Momen; Martens, Kristina; Quadir, Asfia; Pontifex, Carly Sabine; Hanson, Alexandra; Korngut, Lawrence; Pfeffer, Gerald
Abstract: Hereditary spastic paraplegias (HSPs) are a diverse group of genetic conditions with variable severity and onset age. From a neurogenetic clinic, we identified 14 patients with very late-onset HSP, with symptoms starting after the age of 35. In this cohort, sequencing of known genetic causes was performed using clinically available HSP sequencing panels. We identified 4 patients with mutations in SPG7 and 3 patients with SPAST mutations, representing 50% of the cohort and indicating a very high diagnostic yield. In the SPG7 group, we identified novel variants in two patients. We have also identified two novel mutations in the SPAST group. We present sequencing data from cDNA and RT-qPCR to support the pathogenicity of these variants, and provide observations regarding the poor genotype-phenotype correlation in these conditions that should be the subject of future study.